Between the office and the coffee shop: an examination of spaces used for research degree supervision - Doug Specht (Journal of Learning Development in Higher Education, 2022)
The last two decades have seen increased attention given to the role of space within the university campus, with numerous new learning spaces forming part of both the physical and the digital campus. Much of the focus of how these spaces work to create supportive learning environments has been on undergraduate teaching. However, these spaces offer a great opportunity to also enhance the doctoral researcher’s supervision process through the creation of new learning spaces that break away from the traditional office setting. In taking the coffee shop as the antithesis of the office, this paper examines theories around space-making in relation to doctoral research, adding in the experiences of UK doctoral researchers to provoke further thought and discussion about how new spaces within a university and outside the campus might be considered part of the pedagogical approach to supervision. Results suggest that although there is much to be considered, doctoral researchers spend the majority of their time in traditional spaces—where they feel the most comfortable—and become progressively less comfortable the further supervision moves towards public spaces.